2008
DOI: 10.1515/hf.2008.061
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the effective capillary cross-sectional area during the alkaline impregnation of eucalyptus wood

Abstract: Wood diffusion is strongly affected by the effective capillary cross-sectional area (ECCSA), which is the area of paths available for diffusion. The ECCSA varies dynamically according to the conditions and progress of the alkaline action. The alkali diffusion in natural wood is a complex process in the course of which the local transport properties are modified by chemical reactions and swelling. A method was developed which allows the fast determination of ECCSA as a result of the dynamic process. It is based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…As ECCSA A seems to have the same relation for any temperature and pH, it can be considered that the acetyl group content is the determinant for the ECCSA A . This fi nding is in agreement with the previous results (Inalbon and Zanuttini 2008 ), for which, less variables were available.…”
Section: Expression Of Eccsa a Dependence On Variablessupporting
confidence: 93%
See 2 more Smart Citations
“…As ECCSA A seems to have the same relation for any temperature and pH, it can be considered that the acetyl group content is the determinant for the ECCSA A . This fi nding is in agreement with the previous results (Inalbon and Zanuttini 2008 ), for which, less variables were available.…”
Section: Expression Of Eccsa a Dependence On Variablessupporting
confidence: 93%
“…For the determination of the ECCSA, a laboratory conductivity cell and an especially designed frame were used (Inalbon and Zanuttini 2008 ). In the procedure, the wood slice is mounted to the frame to keep it fl at and equidistant from the electrodes.…”
Section: Effective Capillarity Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Introducing cracks to chips may also shorten the transportation path of cooking chemicals with all the beneficial effects (Sainio 2000). The diffusion rate of chemicals increases with increasing temperature (Inalbon and Zanuttini 2008). The viscosity of the impregnation liquor decreases at higher temperatures, which contributes to the impregnation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the ECCSAvalue is not reduced when alkali is removed by washing. As discussed in previous studies, for eucalyptus wood, it depends on the deacetylation degree (Inalbon and Zanuttini 2008) and for pine wood, it depends on both the deacetylation and GGM degradation degree .…”
Section: Initial Concentration (Mol L -1 ) Speciesmentioning
confidence: 62%